J 87 (GG 36): A high yielding Spanish bunch groundnut variety for zone-I: J 87 (GG 36): A high yielding Spanish bunch groundnut variety for zone-I - G K SAPARA; R B MADARIYA; C J RAJANI (Journal of Oilseeds Research, 2023)
Groundnut genotype J-87 was evaluated in AICRP-G trials over the 6 locations and three years during the Rabi/Summer seasons of 2014-15 to 2018-19. Mean pod yield 4165 kg/ha, which was higher than the check varieties viz., TAG 24 (3680 kg/ha), Dh 83 (3671 kg/ha), and SG 99 (3237 kg/ha). Thus, this genotype expressed an overall improvement of 13.18%, 13.45%, and 28.66% in pod yield over the zonal check varieties. J 87 recorded average 100-kernel weight of 63.00 g, shelling out-turn of 71.00% and oil content 50.00%. The damage due to insect pest was at par while diseases showed comparable reactions.